2016
DOI: 10.1155/2016/9063874
|View full text |Cite
|
Sign up to set email alerts
|

Poly(acrylonitrile-co-butadiene-co-styrene) Reinforced with Hollow Glass Microspheres: Evaluation of Extrusion Parameters and Their Effects on the Composite Properties

Abstract: Hollow glass microspheres (HGMs) filled poly(acrylonitrile-co-butadiene-co-styrene) (ABS) composites were prepared by means of a twin-screw extruder. S038 HGMs were incorporated at different percentages of 2.5, 5.0, and 7.5 wt%. The HGMs were added into the twin-screw extruder at two different feeding zones, and the effect of HGMs loading and specific feeding zone addition on the composites produced was evaluated with regard to morphological, thermal, rheological, physical, and mechanical properties. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Furthermore, this result indicates that large-scale polymer relaxations are restrained by the presence of HGM effectively, which agrees with the HDT results. In addition, the incorporation of HGM improves the stiffness of ABS, which is consistent with the results obtained in other studies 11,13,14 .…”
Section: Rheological Propertiessupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, this result indicates that large-scale polymer relaxations are restrained by the presence of HGM effectively, which agrees with the HDT results. In addition, the incorporation of HGM improves the stiffness of ABS, which is consistent with the results obtained in other studies 11,13,14 .…”
Section: Rheological Propertiessupporting
confidence: 92%
“…The HGM are submitted to less shear forces when fed at this zone and therefore maintain their structure during the extrusion process. In our previous study 11 , the HGM were incorporated at the extruder feeding point and the results showed that HGM were broken due to the higher residence time at the extruder associated with higher shear forces of the twin-screw extrusion process. The addition of ABS powder along with the HGM seems to promote better incorporation of the reinforcement by the polymer matrix, however, according to Figure 2 The SEM micrograph of the composite with 5.0 wt.% of HGM and 45 wt.% of high impact ABS is shown in Figure 2(d).…”
Section: Morphological Propertiesmentioning
confidence: 99%
See 3 more Smart Citations